2010
DOI: 10.1002/hep.23571
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepatitis B surface antigen and hepatitis B e antigen titers: Disease phase influences correlation with viral load and intrahepatic hepatitis B virus markers

Abstract: The correlation between quantitative HBsAg titer and serum and intrahepatic markers of HBV replication differs between patients with HBeAg-positive and HBeAg-negative CHB. HBeAg titers may fall independent of viral replication as HBeAg-defective variants emerge prior to HBeAg seroconversion. These findings provide new insights into viral pathogenesis and have practical implications for the use of quantitative serology as a clinical biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

44
315
6
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 376 publications
(373 citation statements)
references
References 33 publications
44
315
6
5
Order By: Relevance
“…17,[19][20][21] Most recently, a thorough investigation that included both qHBsAg and qHBeAg was conducted to identify their relationship with intrahepatic markers of HBV replication, and it suggested potential practical implications for these quantitative serological markers. 24 Our study is the first to report serial qHBeAg values in patients on ETV therapy. We have shown that a decline in qHBeAg is highly predictive for SR with sensitivity and specificity values as high as 75.0% and 89.8%, respectively.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…17,[19][20][21] Most recently, a thorough investigation that included both qHBsAg and qHBeAg was conducted to identify their relationship with intrahepatic markers of HBV replication, and it suggested potential practical implications for these quantitative serological markers. 24 Our study is the first to report serial qHBeAg values in patients on ETV therapy. We have shown that a decline in qHBeAg is highly predictive for SR with sensitivity and specificity values as high as 75.0% and 89.8%, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…First, the mechanism of action of oral nucleos(t)ide analogues is the suppression of viral replication through inhibition of HBV polymerase; because HBsAg production proceeds by a pathway distinct from that of HBV DNA, the effect of ETV on qHBsAg is possibly less prominent. 24 Second, the HBV genotype seems to play a major role in qHBsAg. In a large series of retrospective data by Gish et al, 16 less HBsAg loss was seen in patients with genotype C (0.5%, 1/201) versus patients with genotype A (7.7%, 15/194) or D (8.1%, 7/79).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of serum HBsAg has been shown to reflect the level and transcriptional activity of covalently closed circular (ccc) DNA [6]. However, among HBeAg-negative patients, the relationship between serum HBsAg level and cccDNA is much weaker than that in HBeAg-positive patients [7]. The exact reason for this observation is uncertain, but could be related to the production of HBsAg by integrated HBV surface gene fragments in the host chromosome or the uncoupling on the regulation of HBsAg and HBV DNA production after HBeAg seroconversion.…”
mentioning
confidence: 99%